184 Assessment of virtual teaching for obstetric and gynaecology postgraduate trainees in Northern Ireland. (16th November 2020) - Ferguson, G; McManus, J; Henry, R; Haughey, N
Abstract : Background: Obstetrics and Gynaecology trainees in Northern Ireland attend bi-monthly postgraduate continued medical education (CME). COVID-19 restrictions meant these teaching sessions could not occur. Collaborating with senior trainees we developed a virtual postgraduate teaching series via ZOOM, delivered over two months focusing on key areas of the new Royal College of Obstetricians and Gynaecologists (RCOG) curriculum. Aims: To assess whether virtual teaching is an effective platform to deliver CME for obstetrics and gynaecology trainees in Northern Ireland. Methods: Survey monkey sent to participants, non-participants and consultants exploring experiences and attitudes towards this teaching series. Results: 33 trainees completed the participant survey, with the majority attending 1–2 sessions. Over 50% were first time users of video conference based teaching. 66% felt confident using video-conferencing for learning. 27 participants agreed the pre session reading enhanced learning. All participants agreed CME should be mapped to the RCOG curriculum. 87% of participants agreed that video-conferencing from a location of choosing improves accessibility. 15 trainees completed the non-participant survey, with 93% stating work commitments as the non-attendance reason. Interestingly 2 trainees were unable to work ZOOM. 73% of non-participants agreed that video-conferencing improved accessibility, with 80% stating they would access recorded sessions if unable to attend. 41 consultants completed the survey. 67% had never used video-conferencing to teach doctors. 40% were not confident in sharing presentations and 92% in managing break-out sessions. 34 consultants would deliver CME virtually with 82% having no objections to recording of sessions. Conclusions: Virtual teaching is an appropriate method to provide the necessary volume and quality of postgraduate medical education. Consultants are keen to provide virtual teaching but would benefit from focused training.